Konsep Diri Muhajir Dalam Gaya Hidup Hijrah (Studi Kasus Pada Pria Dewasa Awal) - Izzah, Lailatul; Yuliza, Eva; Putri, Umi Hima (UIR Press, 2023)
Early adulthood is a transitional period from adolescence. At this time the individual has begun to change values ​​that according to him are not by social expectations. Changes in views occur one of them regarding religious values. This process of change is also known as migration. During the migration process, the muhajir (the person who migrated) re-concepts himself with a new concept based on changes from the past and the new values ​​he follows. In this study, researchers used qualitative methods using case studies and collected data through semi-structured interview techniques. Sampling in this study used a non-random sampling technique, with purposive sampling, and obtained one subject with the initials